ANALISIS KESEDIAAN MENERIMA DANA KOMPENSASI DARI KEBERADAAN TEMPAT PEMBUANGAN SAMPAH KECAMATAN RUMBAI PESISIR KOTA PEKANBARU DENGAN CONTINGENT VALUATION METHOD - Dharma, Dewi Kusuma; Eriyati, Eriyati; Nobel, Aqualdo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2020)
This study attempts to 1) know the amount of the compensation funds who are willing to accepted willingness to accept ) the community in subdistrict a Rumbai Pesisir. 2 ) to know what factors affecting the public in receiving value in compensation funds in subdistrict a Rumbai Pesisir. 3 ) to know whether people are willing to receiving value in compensation funds or move the dump. Population in this research is residents in rw 10 to the total number of 469 the heads of households. In the sample collection was used in the study a method of purposive the sampling method of where peniliti determine the sample collection in ways a Special ways consistent with the objectives of research.The methodology that was used with a tool that is descriptive kuantitatis logistic regression analysis and run Logistics and linear regression with income, variable influence and the worship of idols distance, , before that time level of education, the total number of dependants, lot of the cost that is used To cope with the against community members ' willingness to receive the money compensation. Results in this research showed that 1 ) the value wta respondents who produced in this research rp50.366,00 / month. non-competitive purchase will be. 2 ) a variable that influential signifkan against wta is the long distance of a house of the location of a garbage dump levels of education and the total number of dependants. 3 ) based on the above analysis known that the community is obliged to accept a garbage dump with a value of compensation amounting to rp50.366,00 / month. If compensation was not they get so communities prefer to waste disposal in order of place moved from that place.Keywords: WTA, CVM, Garbage Dump